PRODUCTIVITY OF CORN FARMS IN SILANG, CAVITE AND ITS INFLUENCE ON ECONOMIC SUSTAINABILITY - Hermilina Mendoza (The Global Academia Publisher, 2026)
Corn is an essential food however in the Philippines its production remains relatively low. This study investigates the factors affecting farms' productivity and evaluate whether these can influence the economic sustainability of corn farms in Silang, Cavite, Philippines. The result shows that internal and external factors are significantly associated and predictors of economic sustainability. The participants strongly agree on their ability to use physical strength to increase production. It implies a strong reliance on their ability to increase the farms productivity which is key to sustaining the farms. The government should create support systems such as policies, training programs, and financial mechanisms to ensure long-term sustainability of farms.